Wound Management of Pediatric Burns - Greenhalgh, David G. (Seminars in Plastic Surgery, 2024)
The goal for treating pediatric burns is to allow the patient to heal with as little scarring as possible. Compared to older children and adults, very small children have anatomic differences that alter their treatment. They have thinner skin that leads to a higher risk for full-thickness burns. Children also tend to freeze when touching a hot item, so that the prolonged contact also leads to deeper burns. Two healing strategies are needed to treat these wounds. One must optimize reepithelialization in superficial burns to reduce scarring. Deeper burns require skin grafting, but there are techniques, such as the use of “sheet” autograft skin that lead to excellent outcomes. Strategies to treat the massive pediatric burn will also be covered. Finally, there are instances where different strategies are needed to cover exposed bone or tendon. The ultimate goal is to return the skin to as normal a state as possible.
Keywords: children; burns; wound healing; scarring; skin grafts